Identifikasi Jenis Parasit Nematoda Usus Pada Lalapan Sayur Kubis (Brassica oleracea) Mentah - Nurhalimah Nurhalimah; Meida Nugrahalia; Sartini Sartini; Ferdinand Susilo (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2023)
Brassica oleracea includes vegetables that are consumed as raw vegetables. The habit of eating raw vegetables in the form of fresh vegetables needs to be observed, especially if the method of washing them is not good so that there are still nematode eggs in the cabbage. This study aims to determine the type of intestinal nematode parasites found in raw cabbage sold at the MMTC market and at food stalls in Lau Dendang, Percut Sei Tuan District. This research method uses the Univariate Analysis method where the data that has been obtained is easy to simplify. Then the data can be made in tabular form according to laboratory standards. The results showed that there was contamination by intestinal nematode parasites based on the type of sampling location, namely at the MMTC market and at the food stalls in Lau Dendang. In the MMTC market, there were 5 positive samples (33%) containing hookworm larvae (Ancylostoma and Necator) on cabbage and 10 negative samples (66%) on cabbage. Meanwhile, at the food stall in Lau Dendang, there were 2 positive samples (13%) and 13 negative samples (86%) containing hookworm larvae (Ancylostoma and Necator) in cabbage which is a raw vegetable.